Urbanidade à venda: Proposta Arquitetônica de uma Galeria Comercial na quadra 104 Sul em Palmas-TO - Silva, Tayna Cristina Bezerra (Universidade Federal do Tocantins, 2021)
Commercial galleries are like covered trade streets, which provide in addition to the comfort to the public a variety and concentration of the market in one place. The commercial gallery allows pedestrians to permeate freely, crossing from streets to blocks. Within this, the objective of this work is to propose a Commercial Gallery for block 104 South, in the area where the Camelódromo is today, as a way to reinforce a quality found in the place, urbanity. With this, a new architectural layout would contribute as much to the commerce as to the comfort of the users. For the preparation of this project, a bibliographical research was prepared on the concept of Commercial Galleries, its history, in addition to being listed some of the main galleries in the world and in Brazil. All this research had influence in the project, from the location to the architectural form. The main focus of this work was to work on the valorization of the pedestrian through a building that would enhance the existing urbanity in the place. Given this, it is notable that more research is done in this field, that the scale of the pedestrian is thought together with the building for a better functioning of the city.